Becoming Mindful : Integrating Mindfulness Into Your Psychiatric Practice. - Zerbo, Erin (American Psychiatric Publishing, 2016)
Several chapters feature embedded exercises and guided meditations, and an appendix with audio guided meditations and a resource list provides psychiatrists, psychologists, psychiatric residents, social workers, counselors, and nurse practitioners, among others, with readily accessible tools to use in sessions with patients.